Upper and lower airfoil deformation superposition method - CHEN HAO; LU ZHILIANG; GUO TONGQING (2016)
The invention provides an upper and lower airfoil deformation superposition method. The method comprises the following steps: determining and obtaining flexibility matrixes in the centers of aerodynamic grid units of upper and lower airfoils; with a flexibility method, decomposing airfoil structure deformation into superposition of deformations generated under the single action of aerodynamic loads of the upper airfoil and the lower airfoil, and obtaining airfoil structure deformation amounts under the single action of the aerodynamic loads of the upper airfoil and the lower airfoil; according to initial static grid coordinates of the airfoils, obtaining deformation interpolation matrixes between the upper airfoil and the lower airfoil with a surface spline method, wherein the deformation interpolation matrixes between the upper airfoil and the lower airfoil include a deformation interpolation matrix [TUL] from the grid center of the upper airfoil to the grid center of the lower airfoil, an interpolation matrix [TLL] from the grid center of the lower airfoil to grid points of the lower airfoil, and an interpolation matrix [TLU] from the grid center of the lower airfoil to grid points of the upper airfoil; and according to the airfoil structure deformation amounts under the single action of the aerodynamic loads of the upper airfoil and the lower airfoil, and the deformation interpolation matrixes of the upper airfoil and the lower airfoil, determining upper and lower airfoil deformation superposition. According to the method, flexibility method based static aeroelastic CFD/CSD coupling calculation is suitable for any airfoil grid distribution situation.